Photochemical Property of Ethyl Acetate of Salam Stem Cortex (Syzygium polyanthum) - M Najib; R. Arizal Firmansyah; Siti Mukhlisoh Setyawati (Journal of Natural Sciences and Mathematics Research, 2017)
The purpose of this experiment is to understand the photochemical property of ethyl acetate extracted from Salam Stem Cortex (Syzygium polyanthum). The electrochemical test of the sample indicated the existence of secondary metabolic compound, i.e flavonoid, alkaloid, steroid, tannin, fenolat and terpenoid. The secondary metabolic compound was mostly beneficial for pharmacology as a herbal medicine.